Retaining Students to Completion: A Qualitative Study of Institutional Factors - Ruegg, Rachael (Journal of University Teaching and Learning Practice, 2023)
Retaining students until they complete their qualifications is one of the main aims of many higher education institutions. Retention of students is also looked at from different perspectives in the literature. This small, exploratory, narrative enquiry research looks into the experiences of twenty-one domestic students during their first year and a half of a three-year bachelor’s degree at a New Zealand university. The same researcher conducted all the interviews, which were recorded, transcribed and imported to Nvivo for thematic analysis. The researcher attempted to draw comparisons between the students who withdrew from the university within the first year and a half and those who did not in order to gain a deeper understanding of the institutional factors which may be involved in retention of students. Four main themes were found in the interview data, relating to expectations for student effort, guidance provided by instructors, feedback provided on assignments and consistency, which seemed to be significant to the university experience for many students.